Treatment of diabetic wound based on hypoglycemic and antioxidant - Li, Xinyan; Tan, Yang; Li, Jie; Sun, Wei; Wang, Yingshuai; Zhang, Yong (Frontiers in Bioengineering and Biotechnology, 2026)
Diabetic ulcers are among the severe complications of diabetes. The accumulation of hyperglycemia and reactive oxygen species (ROS) in these ulcers significantly delays wound healing. Nanomedicine offers promising advantages for targeted drug delivery and enhanced therapeutic efficacy in treating diabetic ulcers associated with hyperglycemia and ROS. Effective treatment relies on the accessibility of suitable medications and wound dressings. This review summarizes current therapeutic strategies for diabetic skin injuries, focusing on two main categories: drugs (hypoglycemic agents and antioxidants) and drug delivery systems (hydrogels, nanofibers, and microneedle patches). By systematically analyzing these approaches, this review aims to inspire and guide the development of advanced nanomedicines for diabetic wound healing.